TINDAK PIDANA TERORISME DARI PERSPEKTIF HUKUM PIDANA INTERNASIONAL - Rahma Yanti (Universitas Pamulang, 2016)
Terrorism is one of transnational crime base on international conventions. One of national crime which consists of transnational aspects. Transnational crime convention only manage about how to run cooperation to eliminate national crime which across country borders. Terrorism hasn’t consider as International crime because there’s no unification about its definition. Terrorism still consider as a sensitive issue in each country related with rass, etnis, culture, religion, and geographical aspects. Terrorism law enforcement proses is each country positive law jurisdiction and not as International Criminal Court jurisdiction based on Rome Statuta.Keywords: Crime, Terrorism, International Criminal Law